2018
DOI: 10.5603/kp.2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

Adropin and circadian variation of blood pressure

Abstract: Decreased adropin levels were found in the nocturnal hypertensive and non-dipper groups. Adropin and hsCRP were found to be independently associated with a non-dipping pattern. We suggest that decreased levels of adropin in non-dipper hypertensive patients might be associated with a longer duration of exposure to high BP. These results point to a possible future role of adropin in identifying hypertensive patients at higher risk of target organ damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
13
0
3
Order By: Relevance
“…Moreover, Gulen et al, [70] found significantly higher levels of adropin in normotensive patients compared to hypertensive ones with and without target organ damage and they reported that adropin was not correlated with systolic and diastolic blood pressure. However, Bolayır et al, [71] showed decreased adropin levels in nocturnal hypertensive and nondipper hypertensive patients and a strong correlation was found between nighttime blood pressure levels with adropin and hsCRP levels. Animal studies indicated that adropin regulates angiogenesis, increases blood flow and capillary density in an ischemia model [9] .…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, Gulen et al, [70] found significantly higher levels of adropin in normotensive patients compared to hypertensive ones with and without target organ damage and they reported that adropin was not correlated with systolic and diastolic blood pressure. However, Bolayır et al, [71] showed decreased adropin levels in nocturnal hypertensive and nondipper hypertensive patients and a strong correlation was found between nighttime blood pressure levels with adropin and hsCRP levels. Animal studies indicated that adropin regulates angiogenesis, increases blood flow and capillary density in an ischemia model [9] .…”
Section: Discussionmentioning
confidence: 92%
“…In a study of 100 hypertensive individuals, reduced adropin levels were observed in the nocturnal hypertensive and nondipper groups. Adropin was associated with a nondipping pattern, suggesting that adropin may be associated with increased target organ damage 51 . Reduced adropin levels were described in patients with hypertensive disorders complicating pregnancy (HDCP) 9,52 …”
Section: Adropin Regulates Biological Pathways That Are Directly or Imentioning
confidence: 99%
“…Adropin was associated with a nondipping pattern, suggesting that adropin may be associated with increased target organ damage. 51 Reduced adropin levels were described in patients with hypertensive disorders complicating pregnancy (HDCP). 9,52 In haemodialysis (HD) patients, reduced serum levels of adropin were associated with dyslipidemia.…”
Section: Adropin Regulates Biological Pathways That Are Directly Ormentioning
confidence: 99%
“…Alenileşmemiş bir eser, eser sahibinin şahsi alanında olduğundan, haczi de mümkün değildir 62 . Eser sahibinin hakkı, şahsa bağlı bir hak olduğundan üçüncü kişiye devredilemeyen ve haczi de caiz olmayan bir haktır 63 .…”
Section: Gayrimaddi Malvarlığı Unsurlarıunclassified